Constructing memory amidst war: The historical memory group of Colombia (2016)
Between 2007 and 2013, we were part of the Historical Memory Group (GMH), a research group comprising researchers and experts working under the auspices of the National Commission for Reparation and Reconciliation of Colombia. The GMH was tasked under Law 975 with producing a report on the origins and causes of the armed conflict in Colombia. Despite the dominant right-wing political context and the ongoing armed conflict, the GMH enjoyed intellectual and operative autonomy in its research. This article interrogates the dynamics and reasons that served as the basis for the GMH's special sensitivity towards victims; the notion of victim implicit in the research work, with its inclusions and exclusions; and the dilemmas that arose in the group's work. We argue that the GMH can be characterized as an agent of knowledge production about a violent past that was able to articulate comprehensive and plural narratives about violence in Colombia. However, this work was limited by state and institutional dynamics that sought to domesticate and instrumentalize the voices of those who had been systematically silenced. A review of the GMH's work suggests three critical dilemmas that constrain truth-telling mechanisms: the dilemma between opening spaces for truth telling and the safety of those providing testimony; the dilemma around whose victims' voices gain authority in the documentation process; and the risks of institutionalizing a discourse around victims that bestows narrative capital to state and societal institutions. © The Author (2015).